THE EFFECT OF CREDIT RISK AND CAPITAL ADEQUACY RATIO UPON RETURN ON ASSET (A Case Study at Banking Listed in Indonesia Stock Exchange) - Yuli Anwar; Etty Murwaningsari (STIE Binaniaga, 2017)
The aim of study to examine the effect of credit risk as measured by non performing loan, and capital adequacy ratio to profitability level measured by return on assets in banking companies listed in Indonesia Stock Exchange (IDX). This research belongs to causative research. The population in this study is the stateowned banks listed on Indonesia Stock Exchange. The sample of this study is determined by purposive sampling method so that obtained four sample companies. The type of data used is secondary data obtained from www.idx.co.id. The analysis method used is multiple regression analysis, correlation, determination and partial test of hypothesis with t test and simultaneously with F test. Based on the results of multiple regression analysis with 5% significance level, the results of this study conclude: (1) non performing loan has a negative and significant influence on profitability in banking companies listed on Indonesia Stock Exchange (2) capital adequacy ratio positively affect profitability on banking industry listed on Indonesia Stock Exchange. So simultaneously and together it can be concluded that NPL and CAR have an effect on ROA.Keywords: non performing loan, capital adequacy ratio, return on asset